End organ perfusion and pediatric microcirculation assessment - Arteaga, Grace M.; Crow, Sheri (Frontiers in Pediatrics, 2023)
Type: Review Article Cardiovascular instability and reduced oxygenation are regular perioperative critical events associated with anesthesia requiring intervention in neonates and young infants. This review article addresses the current modalities of assessing this population's adequate end-organ perfusion in the perioperative period. Assuring adequate tissue oxygenation in critically ill infants is based on parameters that measure acceptable macrocirculatory hemodynamic parameters such as vital signs (mean arterial blood pressure, heart rate, urinary output) and chemical parameters (lactic acidosis, mixed venous oxygen saturation, base deficit). Microcirculation assessment represents a promising candidate for assessing and improving hemodynamic management strategies in perioperative and critically ill populations. Evaluation of the functional state of the microcirculation can parallel improvement in tissue perfusion, a term coined as "hemodynamic coherence." Less information is available to assess microcirculatory disturbances related to higher mortality risk in critically ill adults and pediatric patients with septic shock. Techniques for measuring microcirculation have substantially improved in the past decade and have evolved from methods that are limited in scope, such as velocity-based laser Doppler and near-infrared spectroscopy, to handheld vital microscopy (HVM), also referred to as videomicroscopy. Available technologies to assess microcirculation include sublingual incident dark field (IDF) and sublingual sidestream dark field (SDF) devices. This chapter addresses (1) the physiological basis of microcirculation and its relevance to the neonatal and pediatric populations, (2) the pathophysiology associated with altered microcirculation and endothelium, and (3) the current literature reviewing modalities to detect and quantify the presence of microcirculatory alterations.